PENGARUH BRAND IMAGE TERHADAP MINAT BELI PRODUK KOSMETIKA WARDAH DI KOTA PAGAR ALAM - Nopera Peronika; Junaidi Junaidi; Yadi Maryadi (Jurnal Ekonomia, 2020)
This research aims to explain: 1. The influence of brand image on buying interest, 2. To find out how much the brand image variable influences buying interest. With a quantitative approach. There are two variables used in this study, namely Brand Image (X) and Buying Interest (Y). Data collection was obtained through the distribution of questionnaires directly to buyers of Wardah Cosmetics Products at the Pagar Alam Square Supermarket in Pagar Alam City. The samples used in this study were 66 respondents using simple linear statistical analysis techniques and incidental sampling techniques. Sampling was carried out on respondents who used Wardah products to find out the magnitude of the influence of brand image on buying interest. The results of a simple linear regression analysis test in this study indicate that the brand image has a positive effect on interest can be seen from the results of a simple regression analysis, namely: Y = 16,191 + 0.578. where a constant value of 16,191 brand image regression coefficient has a positive effect, which means that if the brand image increases by one unit, buying interest will increase by 0.578 units. Brand image has a significant effect on buying interest in Wardah Cosmetics products in Pagar Alam City which are obtained from the results of the t test where the significance value is 0.000, which means it is smaller than 0.05 so the hypothesis is accepted.